Dress and dress code in medieval Cairo - Behrens-Abouseif, Doris, 1946- (Leiden ; Boston)
xvi, 240 sayfa
Keywords: “In this book, Doris Behrens-Abouseif responds to the Mamluk chroniclers whose loquacity regarding clothing matters demands our attention. Using a multiplicity of sources including chronicles, European and Muslim travel narratives, popular storytelling, legal treatises, literature, and poetry, Behrens-Abouseif delves into the details of Mamluk dress. Whether as a vehicle for the sultanate's self-representation both internationally and domestically or as an expression of religious and social identities, status and wealth, female assertion, urban culture, and artistic creativity, clothing personified the broad Mamluk social spectrum. Replete with colorful anecdotes and copious illustrations, Dress and Dress Code in Medieval Cairo offers a lively and comprehensive study of this fascinating topic.“--